Strategi pengembangan kawasan wisata green bay beach di kabupaten Banyuwangi Jawa Timur - Achmad Yanu Alif Fianto; Raissa Daniswara (Universitas Pendidikan Indonesia (UPI), 2022)
One of the strategies to be able to help the tourism industry players, especially marine tourism which is the main potential of the Indonesian tourism industry, is more emphasized on the ability to identify various development possibilities. Therefore, this community service activity is carried out by implementing a series of processes starting from identifying threats and opportunities from the external side as well as weaknesses and strengths on the internal side to the elaboration of community-based tourism development. The series of processes include observation and problem identification, analysis and formulation of tourism development strategies. This community service activity was carried out in the Green Bay Beach Tourism area in Banyuwangi Regency, East Java. This method of implementing community activities is focused on formulating a tourism development strategy based on a Strength, Weakness, Opportunity and Threat (SWOT) analysis. This community service activity resulted in several recommendations for tourism development in the Green Bay Beach Tourism area. The results of the strategy formulation from this activity can be continued in a more holistic community service activity scheme in order to provide insight and knowledge regarding the development of tourism area strategies.